Representation of Sharenting in Rans Entertainment YouTube Content: (Semiotics Analysis of “Banjir Undangan TV!! Raffi Nagita Support Bakat Cipung di Dunia Entertainment, Cipung Anteng Aja.”) - Amira Balqis Sandika; Swita Amallia Hapsari (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2025)
Sharenting or a phenomenon in which parents share their kids’ daily life has become a current trend in social media websites such as YouTube. This trend has  also become famous in Indonesia since two Indonesian public figures, Raffi Ahmad and Nagita Slavina regularly share their sharenting contents on their Rans Entertainment YouTube channel. The researcher aimed to examine one of the sharenting contents of Rans Entertainment sharenting titled "Banjir Undangan TV!! Raffi Nagita Dukung Bakat Cipung di Dunia Entertainment, Cipung Anteng Aja.." through theoretical perspectives of Hall’s representation theory and Pierce’s semiotics approach. We used a descriptive qualitative research design. We used observation and documentation as the research instruments. We observed the scenes from the content and found 12 scenes as the research subjects. The results showed that Cipung's interactions with adults and peers shaped her identity, and created a complex dynamic between privacy, identity and public exposure. The findings highlight the impact of sharenting on children's privacy and the importance of parental awareness in sharing moments of children's lives on social media.